KONSENTRASI MERKURI PADA RAMBUT KEPALA DAN KESEHATAN MASYARAKAT PADA LOKASI PENAMBANGAN EMAS TRADISIONAL BULADU KABUPATEN GORONTALO UTARA - Marike Mahmud; Fitryane Lihawa; Beby Banteng; Frice Desei; Yanti Saleh (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2018)
This study aims to identify mercury concentrations in head hair and its effect on public health at the traditional gold mining. The study was conducted at the gold mining, Buladu Village, North Gorontalo Regency. Samples were taken randomly from human head hair. Samples of public health condition were taken from respondents who served as the samples of mercury concentrations in the head hair. The number of respondents was 20 people. The samples of mercury in the head hair were analyzed at the Integrated Research and Testing Laboratory of UGM by using mercury analyzer. The quality standard used as a reference to the mercury concentrations   in the head hair was the recommendation of the National Research Council (NCR), i.e. 12 ppm. The results of the analysis of the public health were tabulated and then interpreted. The results of the analysis indicated that the highest mercury concentration in the head hair was 952.85 mg/kg and the lowest was 0.03 mg/kg with an average mercury concentration of 55.09 mg/kg. This result was above the threshold quality standards established by NCR, i.e. 12 ppm. Many factors affect the mercury concentrations in humans, including education, income, environmental sanitation and food consumption. Waste dumped directly into the river will affect river water and marine aquatic animals. The consumption of food taken from the waters of Sulawesi Sea affects influence the mercury concentrations in the head hair.